Differential Effect of Metabolic Health and Obesity on Incident Heart Failure: A Nationwide Population-Based Cohort Study - Kim, Hwi Seung; Lee, Jiwoo; Cho, Yun Kyung; Park, Joong-Yeol; Lee, Woo Je; Kim, Ye-Jee; Jung, Chang Hee (Frontiers in Endocrinology, 2021)
Background: Metabolically healthy obese (MHO) individuals and their association with cardiometabolic diseases have remained controversial. We aimed to explore the risk of incident heart failure (HF) based on the baseline metabolic health and obesity status as well as their transition over 2 years. Methods: The Korean National Health Insurance Service-National Health Screening Cohort data of 514,886 participants were analyzed. The incidence of HF was evaluated based on the sixteen categories of dynamic metabolic health and obesity status. Results: The MHO group comprised 9.1% of the entire population and presented a better baseline metabolic profile than the metabolically unhealthy non-obese (MUNO) and metabolically unhealthy obese (MUO) groups. During the median 71.3 months of follow-up, HF developed in 5406 (1.5%) participants. The adjusted hazard ratios (HR [95% CI]) of HF at baseline, compared with the metabolically healthy non-obese (MHNO) group, were 1.29 [1.20–1.39], 1.37 [1.22–1.53], and 1.63 [1.50–1.76] for MUNO, MHO, and MUO groups, respectively. With the stable MHNO group as reference, transition into metabolically unhealthy status (MUNO and MUO) increased the risk of HF, regardless of the baseline status. Subjects who were obese at both baseline and follow-up showed an increased risk of HF, regardless of their metabolic health status. Conclusions: Metabolic health and obesity status and their transition can predict the risk of incident HF. Losing metabolic health in all individuals and remaining obese in baseline obese individuals were significantly associated with increased risk of HF. Maintaining good metabolic health and a lean body may prevent the development of HF.